2017
DOI: 10.1093/mnras/stx2166
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: global stellar populations on the size–mass plane

Abstract: We present an analysis of the global stellar populations of galaxies in the SAMI Galaxy Survey. Our sample consists of 1319 galaxies spanning four orders of magnitude in stellar mass and includes all morphologies and environments. We derive luminosityweighted, single stellar population equivalent stellar ages, metallicities and alpha enhancements from spectra integrated within one effective radius apertures. Variations in galaxy size explain the majority of the scatter in the age-mass and metallicitymass relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 119 publications
9
94
2
Order By: Relevance
“…In further support of this conclusion, Fagioli et al (2016) found that large quiescent field galaxies with 10.5 < Log(M * /M ) < 11 at 0.2 < z < 0.8 were composed of younger stellar populations than smaller quiescent field galaxies within the same stellar mass range. Similar results to this one have also been found by Delaye et al (2014), Gargiulo et al (2017), Scott et al (2017), Williams et al (2017), Zahid & Geller (2017) and Wu et al (2018). van der Wel et al (2014) however did observe a decrease in the number density of compact quiescent galaxies with a much larger sample of field galaxies between 0 < z < 2, concluding that minor mergers drive the observed growth in the average size of quiescent galaxies with decreasing redshift.…”
Section: Recently Quenched Galaxies and Evolution In The Quiescent Masssupporting
confidence: 87%
“…In further support of this conclusion, Fagioli et al (2016) found that large quiescent field galaxies with 10.5 < Log(M * /M ) < 11 at 0.2 < z < 0.8 were composed of younger stellar populations than smaller quiescent field galaxies within the same stellar mass range. Similar results to this one have also been found by Delaye et al (2014), Gargiulo et al (2017), Scott et al (2017), Williams et al (2017), Zahid & Geller (2017) and Wu et al (2018). van der Wel et al (2014) however did observe a decrease in the number density of compact quiescent galaxies with a much larger sample of field galaxies between 0 < z < 2, concluding that minor mergers drive the observed growth in the average size of quiescent galaxies with decreasing redshift.…”
Section: Recently Quenched Galaxies and Evolution In The Quiescent Masssupporting
confidence: 87%
“…The authors found that seven out of the seven gas-phase metallicity indicators exhibit solar and super-solar values in the central region of NGC 2903, even reaching 0.4 dex above so-lar values. It is interesting to note that other radial gradient studies in the low redshift regime (e.g., González Delgado et al 2015;Scott et al 2017) show that the median stellar metallicity trend for galaxies with similar morphology and similar mass to NGC 2903 have slighty below solar stellar metallicity values. This may however be an effect of lower spatial sampling that would drive the average metallicity down.…”
Section: Stars In the Bulgementioning
confidence: 88%
“…According to Taylor et al, this relation provides an estimate of the stellar mass-to-light ratio (M * /Li) to a 1σ accuracy of ∼ 0.1 dex. In addition, to estimate average host galaxy stellar metallicities, we use the Gallazzi et al (2006) correlation between stellar mass of E-S0 galaxy and log(Z * /Z⊙) as determined from about 26000 SDSS galaxies (see also Scott et al 2017, for early-type/high mass galaxies):…”
Section: Sne Ia Locations Vs Fractional Radial Light Distributions Omentioning
confidence: 99%